2017
DOI: 10.1016/j.jneumeth.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gait and sensorimotor deficits in the D1CT-7 mouse model of Tourette syndrome

Abstract: Tourette syndrome (TS) is a neurodevelopmental disorder characterized by multiple motor and phonic tics. While TS patients have been also shown to exhibit subtle abnormalities of sensorimotor integration and gait, animal models of this disorder are seldom tested for these functions. To fill this gap, we assessed gait and sensorimotor integration in the D1CT-7 mouse, one of the best-validated animal models of TS. D1CT-7 mice exhibit spontaneous tic-like manifestations, which, in line with the clinical phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…D1CT‐7 mice exhibit brief (~0.1 seconds), spontaneous stereotypic head or body twitches, which are typically exacerbated by acute stress . These recurring tic‐like movements are accompanied by locomotor hyperactivity, perseverative allogrooming, digging, gnawing and leaping/rearing behaviors, as well as sensorimotor gating deficits and gait impairments . These deficits are consistent with clinical features in patients with TS, supporting the face validity of the dyskinetic manifestations of D1CT‐7 mice as reliable models of tics …”
Section: Introductionmentioning
confidence: 64%
“…D1CT‐7 mice exhibit brief (~0.1 seconds), spontaneous stereotypic head or body twitches, which are typically exacerbated by acute stress . These recurring tic‐like movements are accompanied by locomotor hyperactivity, perseverative allogrooming, digging, gnawing and leaping/rearing behaviors, as well as sensorimotor gating deficits and gait impairments . These deficits are consistent with clinical features in patients with TS, supporting the face validity of the dyskinetic manifestations of D1CT‐7 mice as reliable models of tics …”
Section: Introductionmentioning
confidence: 64%
“…These integrated power values were averaged across low mobility bouts to produce a single measure of integrated power per mouse. Additional measures of “long runs” and “crossings” were scored with the aid of a scrolling graphics program, written in Visual Basic to extract gait parameters that are not included in the commercial software (Fowler et al , 2017; Stanford et al , 2015). Long runs refers to the number of runs for which gait data were calculated (runs had to be long, fast, straight, and continuous with well-formed force-time waveforms), and crossings were counted on the basis of being long and straight (by visual inspection) but not necessarily fast and not having well-formed rhythmic waveforms.…”
Section: Methodsmentioning
confidence: 99%
“…These subtleties increase confidence that the observed behaviors do indeed reflect tic-relevant abnormalities. More recently, further parallels with tics have been documented: hyperkinetic movements in D1CT-7 mice have been shown to be exacerbated by acute stress (Godar et al, 2016), and the mice have been shown to exhibit PPI deficits (Godar et al, 2016) and deficits in sensorimotor integration (Fowler et al, in press). …”
Section: Studying Tic-like Movements Using a Phenomenological Approachmentioning
confidence: 99%
“…The D1CT-7 mice have face validity for tics along several dimensions (Campbell et al, 1999; Fowler et al, in press; Godar et al, 2016; Nordstrom and Burton, 2002), but the case for their relevance is also bolstered by the fact that they recapitulate the corticostriatal hyperactivity associated with tic disorders (Hallett, 2001; Leckman et al, 2010). Similarly, models based on specific pathophysiological hypotheses – local striatal disinhibition; interneuronal pathology; or histamine deficiency – have been validated by the production of repetitive behavior when this pathophysiology is recapitulated in an animal (Bronfeld and Bar-Gad, 2013; Pittenger, 2017a; Xu et al, 2015a; Xu et al, 2016); in several cases this analysis has entailed examination of modulators of tic phenomenology, such as acute stress or psychostimulant challenge (Castellan Baldan et al, 2014; Xu et al, 2015a; Xu et al, 2015b; Xu et al, 2016), providing nuance to the behavioral characterization.…”
Section: Conclusion: Combining Phenomenology- and Pathophysiology-basmentioning
confidence: 99%